Indicadores de estágio sucessional em um fragmento florestal de mata atlântica no sul do Espírito Santo - Paschoa, Luciana de Souza Lorenzoni (2016)
This study aimed to identify more indicators associated to different successional stages in a forest fragment of Atlantic forest that makes up the the Polo forest fragment Environmental Education the IFES - Campus Alegre (PEAMA). To this end, the forest fragment PEAMA (109,6 ha) was divided into three glebes with different ages fallow: glebe 1 (39,47 ha and 46 years of fallow after selective logging), glebe 2 (26,95 ha and 56 years of fallow after cultivation of coffee) and glebe 3 (20,63 ha and 42 fallow years after the abandonment of pastures). We used the fixed area portion method (20 x 20 m), totaling 19 plots (0,76 ha) systematically distributed in the forest fragment PEAMA being: seven plots on glebe 1, six plots in glebe 2 and six plots in glebe 3. All individual trees with DAP=5 cm were sampled and held phytosociological analysis. The diameter structure was compared between plots using the chi-square test. We calculated the rates of diversity Shannon-Wiener (H'), which was compared between glebes by Jackknife estimate, and Pielou evenness (J). We calculated the Sørensen similarity indices and Morisita Horn between glebes. The species were classified as the guilds and the dispersion syndromes. Other variables were sampled, these being: lianas, vertical coverage of lichens and bryophytes/ pteridophytes, both corticicolous, count of vascular epiphytes and macroscopic fungi and chemical analysis and physical soil at depths of 0-10 and 10-20 cm. The glebes were compared using analysis of variance (ANOVA) and discrimination of means by Tukey test when necessary. For the variables that did not meet the requirements of a parametric test, Kruskal-Wallis test was applied and the means were broken down by the Dunn test. Is sampled, among the arboreal individuals, a total of 1772,4 ind ha-1 belonging to 153 species, 91 genera and 33 botanical families. The glebe 2 had the highest abundance (1912 ind ha-1) and 3 glebe the greatest wealth (93). The IX Fabaceae and Meliaceae families were the richest in the three glebes. The index of Shannon-Wiener (H') was 4,22 for the forest fragment PEAMA and between glebes were statistically equal. The Sørensen similarity index showed greater similarity between the glebes 1 and 3 (0,55) and Morisita Horn index formed the first block between glebes 2 and 3 (0,46). The basal area was 29,02 m2 ha-1 for the forest fragment PEAMA and between plots the values were statistically equal. Registered 3003,95 ind ha-1 lianas in total plots, being in glebe 3 found lower abundance (2101 ind ha-1) and a higher proportion of individuals in the second size class (43,6% 2,5 =DAP <5). Found 294,43 m ha-1 lichens and 39,49 m ha-1 bryophytes/ pteridophytes, both corticicolous. Sampled is 794,7 ind ha-1 of macroscopic fungi in the forest fragment PEAMA. The soil chemical analysis showed a trend towards greater acidity in glebe 2 and physical analysis was statistically equal between the glebes. The variables sampled in this study indicated that the plots are in successional processes similar and thus were no longer associated indicators identified at different successional stages in the forest fragment PEAMA.